Clinicoepidemiological Profile and Sexual Behaviour Pattern of Patients with Anogenital Warts - Pandit, Anup; Tangbetani, Laila Lama; Dangol, Nhuchhe Man Singh; Ranjit, Sudina (Nepal Journal of Dermatology, Venereology & Leprology, 2023)
Introduction: Anogenital wart (AGW) is the infection of the anal and genital mucosa and their adjoining areas by Human papilloma virus (HPV) 6, 11. Genital HPV infections are transmitted primarily through sexual contact. This study determines the clinicoepidemiological profile and sexual behavior patterns in patients with AGW. Materials and Methods: A hospital-based descriptive cross-sectional study was conducted in patients diagnosed with AGW attending the Department of Dermatology and Venereology, Bir Hospital between November 2019 and December 2020. Results: A total of 77 patients including 58 males and 19 females diagnosed with AGW were studied. The warts were recorded more commonly in married individuals (62.3%). The most common sites of warts were penis (84.5% of males) and vulva (57.9% of females) followed by perianal skin, and perineum in both males and females. Of the various morphologies, dome shaped warts were most commonly observed (58.6% in males and 73.7% in females). The individuals with extramarital contacts were at significantly more risk of AGW than those without such contacts (P =0.001). AGW cases were seen more frequent in patients with syphilis and HIV (7.8% and 2.6% respectively) compared to general population. Conclusion: Genital warts were more common in 16 – 25 years of age, mostly married, and polygamous. Like all STD (sexually transmitted diseases), Genital warts (GWs) have important effects on the health of society and quality of life. Hence, awareness of the clinical presentations, sexual aspects, and possible risk factors of GWs leads to the use of effective protection measures.